Integrating Islamic Principles and Modern Counseling Approaches in Managing Family Crises: Evidence from Northwestern Nigeria - Kabiru Uba Ibrahim; Amb. Usman Mallam Hussaini; Auwal Salisu; Abubakar Siddiq Uba (RaSAIL Media Group, Semarang, Indonesia, 2025)
This study makes family crisis management in Muslim families in the Northwestern region of Nigeria a tangible subject, with an emphasis on integrating Islamic principles and modern counseling approaches. The objectives of this study are to identify the primary causes of family crisis, examine relevant Islamic teachings on family conflict resolution, analyze contemporary approaches to managing family crises, and assess the effectiveness of integrated models that combine spiritual, moral, and psychological dimensions. This study uses a descriptive qualitative design with purposive sampling techniques involving Muslim couples, scholars, family counselors, and social workers. Data were collected through semi-structured interviews, focus group discussions (FGDs), and document analysis, then analyzed using thematic analysis techniques. The study's results indicate that family crises are often triggered by economic pressure, communication failures, and a lack of understanding of marital responsibilities. Islamic principles, such as sabr (patience), shura (consultation), and rahmah (compassion), have proven crucial in defusing conflicts and fostering family harmony. Modern approaches, particularly cognitive-behavioral therapy and structured family counseling, can help improve communication and emotional management. This research contributes by offering a culturally sensitive, integrative model that links Islamic ethics and modern psychology, providing practical implications for family counselors, religious institutions, and policymakers in strengthening the resilience of Muslim families. This study makes family crisis management in Muslim families in the Northwestern region of Nigeria a tangible subject, with an emphasis on integrating Islamic principles and modern counseling approaches. The objectives of this study are to identify the primary causes of family crisis, examine relevant Islamic teachings on family conflict resolution, analyze contemporary approaches to managing family crises, and assess the effectiveness of integrated models that combine spiritual, moral, and psychological dimensions. This study uses a descriptive qualitative design with purposive sampling techniques involving Muslim couples, scholars, family counselors, and social workers. Data were collected through semi-structured interviews, focus group discussions (FGDs), and document analysis, then analyzed using thematic analysis techniques. The study's results indicate that family crises are often triggered by economic pressure, communication failures, and a lack of understanding of marital responsibilities. Islamic principles, such as sabr (patience), shura (consultation), and rahmah (compassion), have proven crucial in defusing conflicts and fostering family harmony. Modern approaches, particularly cognitive-behavioral therapy and structured family counseling, can help improve communication and emotional management. This research contributes by offering a culturally sensitive, integrative model that links Islamic ethics and modern psychology and provides practical implications for family counselors, religious institutions, and policymakers in strengthening the resilience of Muslim families.